Spirituality and Moral Sensitivity of Undergraduate Nursing Students STIKES Santa Elisabeth Medan - Imelda Derang; Lilis Novitarum; Malensi Rajagukguk (Journal of Nursing Science Update (JNSU), 2022)
Nursing is an important factor of all professional services, including Bio, Psycho, Socio, and Spiritual, which must be possessed because it is a crucial aspect of service, especially for the people we serve. This is because moral sensitivity and a strong sense of spirituality can assist someone in interpreting changes in their daily lives in light of God, the environment, and themselves. This study aims to determine the relationship between spirituality and moral sensitivity of undergraduate nursing students at STIKes Santa Elisabeth Medan T.A 2021/2022. We used a cross-sectional design. The sampling technique in this study used purposive sampling. The numbers of respondents are 358 respondents. The instrument used was a spirituality and moral sensitivity questionnaire for nursing students (MSQ-ST). The findings revealed great moral sensitivity (87.4%) and spirituality (82.4%). According to the findings of the Spearman Rank statistical test (rho), r = (.271) and p (value) = 0.000 (p 0.05) were obtained. These results indicate a weak relationship between the two variables with a positive direction, meaning that the higher the spirituality level of the students, the higher the moral sensitivity of nursing students at STIKes Santa Elisabeth Medan.